Si / SiOx / C composite material and preparation method and application thereof
By designing a Si/SiOx/C composite material, which includes a carbon matrix loaded with silicon particles, a metal silicate core and a carbon coating layer, the volume expansion and cycle stability problems of silicon-based negative electrodes were solved, and the electrochemical performance of lithium-ion batteries was improved.
Patent Information
- Application Number
- CN202510960683.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-11
- Publication Date
- 2025-10-21
AI Technical Summary
The silicon-based negative electrode materials in existing lithium-ion batteries have problems of severe volume expansion and poor cycle stability, which limits their industrial application.
A Si/SiOx/C composite material was designed, including a carbon matrix loaded with silicon particles, SiOx and a metal silicate core, and a coating layer of carbon material was partially coated on the surface. The core improves the expansion effect and forms a stable SEI film, while the outer layer of carbon material blocks the reaction between the core and the electrolyte, thereby improving conductivity.
It significantly improves the cycle stability and conductivity of silicon-based negative electrodes, improves charge and discharge performance, extends battery life and increases the first coulombic efficiency.
Smart Images

Figure CN120824339A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the technical field of battery materials, specifically, to a Si / SiO x / C composite material and its preparation method and application. Background Art
[0002] Lithium-ion batteries have been widely used in industrial production and daily life due to their stable output, high energy density, and portability. Generally, lithium-ion batteries are composed of a positive electrode, a negative electrode, an electrolyte, a separator, a current collector, and a battery shell. Among them, the negative electrode material is one of the key materials that determines the energy density of lithium-ion batteries. At present, commercial lithium-ion batteries usually use graphite as the battery negative electrode, thanks to its stable discharge voltage platform, good cycle performance, and low preparation cost. However, the limited intrinsic theoretical capacity of the graphite negative electrode (372mAh / g) restricts its application in further improving the battery energy density.
[0003] Silicon-based anodes have been widely studied due to their ultra-high theoretical capacity, but currently they still suffer from problems such as severe volume expansion (≥300%), rapid capacity decay, excessive electrolyte consumption, and poor cycle stability, which seriously limit their industrialization process. Summary of the Invention
[0004] The main purpose of this application is to provide a Si / SiO x / C composite material and its preparation method and application are used to solve the problem of poor cycle stability of silicon-based negative electrodes in the prior art.
[0005] In order to achieve the above object, according to the first aspect of the present application, a Si / SiO x / C composite material, which includes a core and a coating layer located on at least part of the surface of the core, wherein the core material includes a carbon matrix and silicon particles, SiO x and metal silicates; the metal silicates include at least one of alkali metal silicates, alkaline earth metal silicates, aluminum silicates, titanium silicates, and zinc silicates.
[0006] By Si / SiO x The structure of the Si / C composite material is designed, which is beneficial to improving the cycle stability of the silicon-based negative electrode on the one hand, and on the other hand, it is beneficial to improving the conductivity of the silicon-based negative electrode and improving its charge and discharge performance.
[0007] Furthermore, the alkali metal silicate is at least one of potassium silicate and sodium silicate.
[0008] Furthermore, the alkaline earth metal silicate is at least one of magnesium silicate and calcium silicate.
[0009] Furthermore, the average particle size of the silicon particles is 10 nm to 5000 nm.
[0010] Furthermore, SiO x The average particle size is 20nm~5000nm.
[0011] Furthermore, the average particle size of the metal silicate is 30 nm to 5000 nm.
[0012] Furthermore, the average thickness of the coating layer is 0.02 μm to 20 μm.
[0013] Furthermore, Si / SiO x The average particle size of the / C composite material is 0.05μm to 30μm.
[0014] According to the second aspect of the present application, there is provided a Si / SiO x A method for preparing a / C composite material comprises the following steps:
[0015] S1, mixing the ash-containing raw material with nano-silicon powder to obtain a first precursor;
[0016] S2, sintering the first precursor under nitrogen or inert gas, crushing and sieving to obtain the Si / SiOx / C composite material;
[0017] In S2, the temperature of the first sintering treatment is 900° C. to 1500° C., and the time is 70 min to 300 min.
[0018] Among them, the mass fraction of ash in the ash-containing raw material is 20% to 40%; the mass fraction of carbon element in the ash-containing raw material is 55% to 80%, the mass fraction of silicon dioxide in the ash is 10% to 20%, and the mass fraction of metal oxides in the ash is 60% to 70%, and the metal oxides include at least one of alkali metal oxides, alkaline earth metal oxides, aluminum oxide, titanium oxide, and zinc oxide.
[0019] Furthermore, the ash-containing raw material is at least one of coal liquefaction oil residue extract, coal, coal tar, and petroleum asphalt.
[0020] Furthermore, the average particle size of the nano silicon powder is 10 nm to 5000 nm.
[0021] Furthermore, the alkali metal oxide includes at least one of potassium oxide and sodium oxide; and the alkaline earth metal oxide includes at least one of magnesium oxide and calcium oxide.
[0022] Furthermore, the mass ratio of the ash-containing raw material to the nano-silicon powder is (1-10):1.
[0023] Furthermore, in S1, the ash-containing raw material is mixed with the nano-silicon powder by wet ball milling.
[0024] Furthermore, in S2, the inert gas is at least one of argon and helium.
[0025] Furthermore, in S2, screening is performed using a sieve with a mesh size of 150 to 350 meshes.
[0026] According to the third aspect of the present application, there is also provided a Si / SiO x A method for preparing a composite material of WO2011 / 05020 comprises the following steps:
[0027] S1, mixing the ash-containing raw material with nano-silicon powder to obtain a first precursor;
[0028] S2, performing a first sintering treatment on the first precursor under nitrogen or a first inert gas to obtain a second precursor;
[0029] S3, acid-washing, water-washing, and filtering the second precursor to obtain a third precursor;
[0030] S4, mixing the third precursor, asphalt, and oxide to obtain a fourth precursor;
[0031] S5, performing a second sintering treatment on the fourth precursor under nitrogen or a second inert gas, crushing and sieving to obtain a Si / SiOx / C composite material;
[0032] In S2, the temperature of the first sintering treatment is 900° C. to 1500° C., and the time is 70 min to 300 min.
[0033] Among them, the mass fraction of ash in the ash-containing raw material is 20% to 40%, the mass fraction of carbon element in the ash-containing raw material is 55% to 80%, the mass fraction of silicon dioxide in the ash is 10% to 20%, and the mass fraction of metal oxides in the ash is 60% to 70%. The metal oxides include at least one of a first alkali metal oxide, a first alkaline earth metal oxide, aluminum oxide, titanium oxide, and zinc oxide; the oxides include at least one of a second alkali metal oxide, a second alkaline earth metal oxide, aluminum oxide, titanium oxide, and zinc oxide.
[0034] Furthermore, the ash-containing raw material is at least one of coal liquefaction oil residue extract, coal, coal tar, and petroleum asphalt.
[0035] Furthermore, the average particle size of the nano silicon powder is 10 nm to 5000 nm.
[0036] Furthermore, the first alkali metal oxide and the second alkali metal oxide each independently include at least one of potassium oxide and sodium oxide; the first alkaline earth metal oxide and the second alkaline earth metal oxide each independently include at least one of magnesium oxide and calcium oxide.
[0037] Furthermore, the asphalt includes at least one of coal liquefaction asphalt, petroleum asphalt, coal tar asphalt, synthetic asphalt, and natural asphalt.
[0038] Furthermore, the mass ratio of the ash-containing raw material to the nano-silicon powder is (1-10):1.
[0039] Furthermore, the mass ratio of the third precursor, asphalt, and oxide is (1-10):(1-3):1.
[0040] Furthermore, in S1, the ash-containing raw material is mixed with the nano-silicon powder by wet ball milling.
[0041] Furthermore, in S1, the ash-containing raw material is mixed with the nano-silicon powder by wet ball milling, wherein the solvent of the wet ball milling is at least one of alcohol, ketone, ester, alkane, and aromatic hydrocarbon.
[0042] Furthermore, the first inert gas and the second inert gas are each independently at least one of argon and helium.
[0043] Furthermore, the screening is performed using a sieve with a mesh size of 150 to 350 meshes.
[0044] Furthermore, in S3, the pickling solution is at least one of hydrochloric acid, nitric acid, formic acid, and acetic acid.
[0045] Furthermore, in S4, the third precursor, asphalt, and oxide are mixed by ball milling.
[0046] Furthermore, in S5, the temperature of the second sintering treatment is 850°C to 950°C, and the time is 2.5h to 7.5h.
[0047] According to the fourth aspect of the present application, there is provided a Si / SiO x Application of Si / SiO / C composite materials in negative electrode materials x The Si / SiO / C composite material is the first aspect of the present application. x / C composite material, or Si / SiO prepared by the preparation method of the second aspect or the third aspect of the present application x / C composite materials.
[0048] Apply the technical solution of this application to Si / SiO x The structure of the C / C composite material is designed to include a carbon matrix and silicon particles, SiO2 and other nanostructured carbon nanotubes loaded on the carbon matrix. x The core is made of a material containing a metal silicate, and a coating layer containing a carbon material is coated on at least part of the surface of the core. On the one hand, the SiO x and metal silicates to improve the expansion effect and increase Si / SiOx / C composite materials; on the other hand, the carbon material in the coating layer can be used to block the core and the electrolyte, avoiding side reactions between the core and the electrolyte, thereby improving the structural stability, capacity and first coulombic efficiency of the negative electrode material; on the other hand, carbon materials can help improve the Si / SiO x / C composite materials, improve the conductivity of lithium ions, and thus improve the Si / SiO x / C composite materials are used in the charge and discharge performance of negative electrode materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0049] Figure 1 In one embodiment of the present application, Si / SiO x Schematic diagram of the preparation process of / C composite materials.
[0050] The following reference numerals are present in the above drawings:
[0051] A. Ash-containing raw material; B. Nano-silicon powder; C. Abrasive; D. First precursor; E. Third precursor; F. Asphalt; G. Oxide. DETAILED DESCRIPTION
[0052] To make the purpose, technical solutions and advantages of the examples of the present application clearer, the technical solutions in the examples of the present application will be described clearly and completely below. Where specific conditions are not specified in the examples, conventional conditions or conditions recommended by the manufacturer are used. Where the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be purchased commercially.
[0053] As described in the background of this application, the expansion rate of silicon-based negative electrodes in the prior art is high and the cycle stability is poor, which hinders the application of silicon-based negative electrodes. In order to solve the above problems, in the first typical embodiment of this application, a Si / SiO x / C composite material, which includes a core and a coating layer located on at least part of the surface of the core, wherein the core material includes a carbon matrix and silicon particles, SiO x and metal silicate; the metal silicate includes at least one of alkali metal silicate, alkaline earth metal silicate, aluminum silicate, titanium silicate, and zinc silicate; the first coating layer is located between the core and the second coating layer.
[0054] In this embodiment, the carbon matrix and the silicon particles, SiO x The materials with metal silicate as the core can significantly improve the electrochemical performance of the composite material. First, the presence of metal silicate helps to form a stable SiO xphase, thereby improving the cycle stability and lithium storage capacity of the composite material; in addition, the presence of metal silicate helps to form a denser SEI film, reducing the irreversible capacity during the first charge and discharge process. In addition, metal silicate also helps to improve the mechanical structure of the composite material, enhancing the mechanical strength and stability of the composite material; the presence of the carbon matrix helps to improve the conductivity and structural stability of the composite material, on the one hand, helps to improve the rate performance of the battery, on the other hand, helps to reduce the cracking and pulverization during the battery cycle, and prolong the cycle life of the battery. The carbon material in the coating layer helps to reduce the probability of contact between the core and the electrolyte, avoid side reactions between the core and the electrolyte, and help to improve the Si / SiO x / C composite materials, and improve their charge and discharge performance. x The structure of the C / C composite material is designed and its application in negative electrode materials can significantly improve its electrochemical performance, cycle stability and first coulombic efficiency.
[0055] In some embodiments, the alkali metal silicate is at least one of potassium silicate and sodium silicate; the alkaline earth metal silicate is at least one of magnesium silicate and calcium silicate.
[0056] The above-mentioned alkali metal silicates and alkaline earth metal silicates help the negative electrode material to form a stable SEI film during the first charge and discharge cycle. The stable SEI film can reduce electrolyte decomposition and irreversible capacity loss, thereby helping to improve the first charge and discharge efficiency of the battery.
[0057] In some embodiments, the average particle size of the silicon particles is 10 nm to 5000 nm.
[0058] Controlling the average particle size of silicon particles within the above range is beneficial to shortening the diffusion path of lithium ions, and can effectively absorb and disperse the stress generated by volume changes during the cycle, preventing the material from cracking and pulverizing, thereby improving the cycle stability and service life of the composite material.
[0059] In some embodiments, SiO x The average particle size is 20nm~5000nm.
[0060] Control SiO x The average particle size of SiO2 in the above range can make closer interface contact with the carbon matrix in the core, thereby promoting the conduction of electrons in the composite material and improving the conductivity and energy conversion efficiency of the battery. x It helps to form a more uniform and stable SEI film, improve the coulombic efficiency of the first charge and discharge, and reduce the irreversible capacity loss of the battery.
[0061] In some embodiments, the average particle size of the metal silicate is 30 nm to 5000 nm.
[0062] During the battery cycle, silicon particles will undergo significant volume changes. Controlling the average particle size of metal silicates within the above range helps to form a small buffer area, effectively absorb and disperse the stress caused by volume changes, reduce crack formation, maintain the structural integrity of the composite material, and thus improve the mechanical stability and cycle life of the material.
[0063] In some embodiments, the average thickness of the coating layer is 0.02 μm to 20 μm.
[0064] Controlling the average thickness of the coating layer within the above range can, on the one hand, effectively isolate the direct contact between the electrolyte and the active material, thereby improving the initial coulombic efficiency and cycle stability; on the other hand, it can also enhance the conductivity of the composite material and improve the rate performance of the battery.
[0065] In some embodiments, Si / SiO x The average particle size of the / C composite material is 0.05μm to 30μm.
[0066] Controlling the composite material's average particle size within the aforementioned range helps shorten the lithium ion diffusion path, increasing the battery's power density. It also helps disperse the stress generated by volume changes during cycling, improving the composite material's cycling stability and durability. Furthermore, the composite material exhibits excellent processability, facilitating the formation of a uniform electrode layer during the coating process.
[0067] In some embodiments, x is 0 to 2 and is not 0.
[0068] When x satisfies the above definition, SiO x It shows high lithium storage capacity and good cycle performance, which helps to improve the Si / SiO x Comprehensive electrochemical performance of / C composites.
[0069] In the second typical embodiment of the present application, a Si / SiO x A method for preparing a / C composite material comprises the following steps:
[0070] S1, mixing the ash-containing raw material with nano-silicon powder to obtain a first precursor;
[0071] S2, sintering the first precursor under nitrogen or inert gas, crushing and sieving to obtain the Si / SiOx / C composite material;
[0072] In S2, the temperature of the first sintering treatment is 900° C. to 1500° C., and the time is 70 min to 300 min.
[0073] Among them, the mass fraction of ash in the ash-containing raw material is 20% to 40%; the mass fraction of carbon element in the ash-containing raw material is 55% to 80%; the mass fraction of silicon dioxide in the ash is 10% to 20%; the mass fraction of metal oxides in the ash is 60% to 70%, and the metal oxides include at least one of alkali metal oxides, alkaline earth metal oxides, aluminum oxide, titanium oxide, and zinc oxide.
[0074] Ash-containing raw materials usually contain a high proportion of ash and carbon elements. Among them, ash is rich in silicon dioxide and other metal oxides. By mixing with nano-silicon powder, the silicon dioxide and metal oxides in the raw materials are utilized without the introduction of additional silicon sources or catalysts, achieving the effects of self-doping and self-catalysis. The silicon dioxide in the ash-containing raw materials can undergo a disproportionation reaction with the nano-silicon powder under the action of metal oxides to generate SiO with a certain lithium storage capacity and a low expansion effect during charging and discharging. x In addition, metal oxides can also react with silicon dioxide to form silicates, thereby obtaining a carbon matrix and a carbon matrix loaded with silicon particles, SiO x The core of the metal silicate is beneficial to inhibit the volume expansion of the core during charge and discharge, and improve the Si / SiO x In addition, the carbon element in the ash-containing raw material can further form a carbon matrix and a coating layer covering at least part of the surface of the core after calcination. The coating layer can protect the core and prevent it from reacting with the electrolyte, thereby improving the cycle stability of the Si / SiO composite material. x The cycling stability and first coulombic efficiency of Si / SiO composites can also be improved. x / C composite materials, improve the conductivity of lithium ions in the Si / SiO x / C composites, improving the embedding and extraction efficiency of Si / SiO x The preparation method is simple and suitable for industrial application.
[0075] In some embodiments, the ash-containing raw material is at least one of coal liquefaction oil residue extract, coal, coal tar, and petroleum asphalt; further, it is coal liquefaction oil residue extract; coal liquefaction oil residue extract is a by-product left in the process of preparing coal liquefaction asphalt products. On the one hand, it contains a large amount of asphaltene, which can provide a natural binder and form a good carbon coating layer after high-temperature sintering, thereby improving the conductivity of the material, inhibiting the expansion effect of silicon, and improving the Si / SiO x / C composite materials have good cyclic stability; on the other hand, it contains silicon dioxide and metal oxides, which are beneficial to the self-catalytic disproportionation reaction and reduce SiO xThe activation energy required in the synthesis process can be reduced, thereby effectively lowering the sintering temperature, improving the reaction efficiency and reducing energy consumption; on the other hand, it can achieve effective utilization of resources.
[0076] In some embodiments, the average particle size of the nano-silicon powder is 10 nm to 5000 nm.
[0077] The nano silicon powder has high activity and can react quickly with silicon dioxide in ash-containing raw materials to form SiO x ; It is also beneficial to shorten the diffusion path of lithium ions, increase the rate of lithium ion insertion and extraction during charge and discharge, and improve the power characteristics of the battery; In addition, nano-scale silicon powder, due to its smaller size and higher elastic modulus, can absorb more stress during charge and discharge, reducing the Si / SiO x / C composite materials to reduce the probability of cracking and powdering, and improve their cycle stability and service life.
[0078] In some embodiments, the alkali metal oxide includes at least one of potassium oxide and sodium oxide; the alkaline earth metal oxide includes at least one of magnesium oxide and calcium oxide. The above alkali metal oxide and alkaline earth metal oxide have good catalytic effects, which help to fully carry out the disproportionation reaction between nano-silicon powder and silicon dioxide; in addition, the metal silicate formed after the sintering of the above alkali metal oxide and alkaline earth metal oxide can effectively reduce the Si / SiO x / C composite material expansion rate during the charge and discharge cycle, further improving the Si / SiO x Cycling stability of the / C composites.
[0079] In some embodiments, the mass ratio of the ash-containing raw material to the nano-silicon powder is (1-10):1.
[0080] Controlling the mass ratio of ash-containing raw materials and nano-silicon powder within the above range is helpful to form a core with appropriate particle size and a coating layer with moderate thickness, which helps to balance the Si / SiO x Capacity, first coulombic efficiency and cycling performance of / C composites.
[0081] In some embodiments, in S1, the ash-containing raw material and the nano-silicon powder are mixed by wet ball milling.
[0082] For nanomaterials, wet ball milling can help ensure full contact and uniform dispersion of the components at the microscopic scale, and its operation is highly controllable and safe.
[0083] In some embodiments, the solvent for wet ball milling is at least one of an alcohol, a ketone, an ester, an alkane, and an aromatic hydrocarbon. The alcohol includes at least one of methanol and ethanol, the ketone includes at least one of acetone and methyl ethyl ketone, the ester includes ethyl acetate, the alkane includes at least one of pentane and hexane, and the aromatic hydrocarbon includes at least one of benzene and toluene. These solvents have good dispersibility for the ash-containing raw material and the nano-silicon powder and are easily removed.
[0084] Typically but not limiting, in S2, the inert gas is at least one of argon and helium.
[0085] In some embodiments, in S2, sieving is performed using a sieve with a mesh size of 150 to 350 meshes. Controlling the mesh size of the sieve within the above range helps to obtain Si / SiO particles with a suitable particle size. x / C composite materials, Si / SiO prepared under the above conditions x The Si / SiO composite material has good processing properties, which is conducive to forming an electrode slurry with good fluidity, forming an electrode with uniform component distribution, and ensuring the integrity and consistency of the electrode material. x The / C composite material has good mechanical stability and can effectively control volume changes and reduce internal stress during the charge and discharge process, while maintaining good electronic conductivity, thereby improving its cycle stability and charge and discharge performance at high rates.
[0086] In the third typical embodiment of the present application, a Si / SiO x The preparation method of / C composite material, the flow diagram of which is as follows Figure 1 As shown, the following steps are included:
[0087] S1, mixing the ash-containing raw material with nano-silicon powder to obtain a first precursor;
[0088] S2, performing a first sintering treatment on the first precursor under nitrogen or a first inert gas to obtain a second precursor;
[0089] S3, acid-washing the second precursor, then washing with water until the washing liquid is neutral, filtering, and drying to obtain a third precursor;
[0090] S4, mixing the third precursor, asphalt, and oxide to obtain a fourth precursor;
[0091] S5, performing a second sintering treatment on the fourth precursor under nitrogen or a second inert gas, crushing and sieving to obtain a Si / SiOx / C composite material;
[0092] In S2, the temperature of the first sintering treatment is 900° C. to 1500° C., and the time is 70 min to 300 min.
[0093] Among them, the mass fraction of ash in the ash-containing raw material is 20% to 40%, the mass fraction of carbon element in the ash-containing raw material is 55% to 80%, the mass fraction of silicon dioxide in the ash is 10% to 20%, and the mass fraction of metal oxides in the ash is 60% to 70%. The metal oxides include at least one of a first alkali metal oxide, a first alkaline earth metal oxide, aluminum oxide, titanium oxide, and zinc oxide; the oxides include at least one of a second alkali metal oxide, a second alkaline earth metal oxide, aluminum oxide, titanium oxide, and zinc oxide.
[0094] Compared with the preparation method in the second embodiment of the present application, the preparation method in the third embodiment further performs pickling and sintering again; in this embodiment, the pickling can remove impurities such as iron and nickel in the second precursor, reduce Si / SiO x / C composite materials, avoiding irreversible side reactions during charge and discharge, and improving the Si / SiO x / C composite materials cycle stability; In addition, acid washing will wash away part of the metal silicate, and by adding oxides, it helps to fill the missing amount of metal silicate, ensuring the Si / SiO x / C composite materials have low expansion rate and high structural stability; adding pitch again for sintering helps to form a stable carbon coating layer, improving the Si / SiO x / C composite material service life and rate performance.
[0095] In some embodiments, the ash-containing raw material is at least one of coal liquefaction oil residue extract, coal, coal tar, and petroleum asphalt; further, it is coal liquefaction oil residue extract; coal liquefaction oil residue extract is a by-product left in the process of preparing coal liquefaction asphalt products. On the one hand, it contains a large amount of asphaltene, which can provide a natural binder and form a good carbon coating layer after high-temperature sintering, thereby improving the conductivity of the material, inhibiting the expansion effect of silicon, and improving the Si / SiO x / C composite materials have good cyclic stability; on the other hand, it contains silicon dioxide and metal oxides, which are beneficial to the self-catalytic disproportionation reaction and reduce SiO x The activation energy required in the synthesis process can be reduced, thereby effectively lowering the sintering temperature, improving the reaction efficiency and reducing energy consumption; on the other hand, it can achieve effective utilization of resources.
[0096] In some embodiments, the average particle size of the nano-silicon powder is 10 nm to 5000 nm.
[0097] The nano silicon powder has high activity and can react quickly with silicon dioxide in ash-containing raw materials to form SiO x; It is also beneficial to shorten the diffusion path of lithium ions, increase the rate of lithium ion insertion and extraction during charge and discharge, and improve the power characteristics of the battery; In addition, nano-scale silicon powder, due to its smaller size and higher elastic modulus, can absorb more stress during charge and discharge, reducing the Si / SiO x / C composite materials to reduce the probability of cracking and powdering, and improve their cycle stability and service life.
[0098] In some embodiments, the first alkali metal oxide and the second alkali metal oxide each independently include at least one of potassium oxide and sodium oxide; the first alkaline earth metal oxide and the second alkaline earth metal oxide each independently include at least one of magnesium oxide and calcium oxide.
[0099] The first alkali metal oxide, the second alkali metal oxide, the first alkaline earth metal oxide and the second alkaline earth metal oxide have good catalytic effects, which help to fully carry out the disproportionation reaction between nano-silicon powder and silicon dioxide; in addition, the metal silicate formed after the sintering of the alkali metal oxide and the alkaline earth metal oxide can effectively reduce the Si / SiO x / C composite material expansion rate during the charge and discharge cycle, further improving the Si / SiO x Cycling stability of the / C composites.
[0100] In some embodiments, the asphalt includes at least one of coal liquefaction asphalt, petroleum asphalt, coal tar asphalt, synthetic asphalt, and natural asphalt. The use of the above asphalt for secondary coating is beneficial to make up for the surface defects formed after pickling and reduce the Si / SiO x / C composite material to increase its specific surface area and improve its first coulombic efficiency.
[0101] In some embodiments, the mass ratio of the ash-containing raw material to the nano-silicon powder is (1-10):1.
[0102] Controlling the mass ratio of ash-containing raw materials and nano-silicon powder within the above range is helpful to form a core with appropriate particle size and a coating layer with moderate thickness, which helps to balance the Si / SiO x Capacity, first coulombic efficiency and cycling performance of / C composites.
[0103] In some embodiments, the mass ratio of the third precursor, pitch, and oxide is (1-10):(1-3):1.
[0104] In some embodiments, in S1, the ash-containing raw material and the nano-silicon powder are mixed by wet ball milling.
[0105] The wet ball milling method helps to ensure that the components are fully contacted and evenly dispersed at the microscopic scale, and the operation is highly controllable and safe.
[0106] In some embodiments, in S1, the ash-containing raw material and the nano-silicon powder are mixed using wet ball milling, wherein the solvent for the wet ball milling is at least one of an alcohol, a ketone, an ester, an alkane, and an aromatic hydrocarbon; wherein the alcohol includes at least one of methanol and ethanol, the ketone includes at least one of acetone and methyl ethyl ketone, the ester includes ethyl acetate, the alkane includes at least one of pentane and hexane, and the aromatic hydrocarbon includes at least one of benzene and toluene. These solvents have good dispersibility for the ash-containing raw material and the nano-silicon powder and are easily removed.
[0107] Typically, but not limiting, the first inert gas and the second inert gas are each independently at least one of argon and helium.
[0108] In some embodiments, the screening is performed using a sieve having a mesh size of 150 to 350 meshes.
[0109] Controlling the mesh size of the sieve within the above range helps to obtain Si / SiO particles with appropriate particle size. x / C composite materials, Si / SiO prepared under the above conditions x / C composite materials have good processing properties, which is conducive to forming electrode slurry with good fluidity, forming electrodes with uniform component distribution, and ensuring the integrity and consistency of electrode materials; In addition, the above Si / SiO x The / C composite material has good mechanical stability and can effectively control volume changes and reduce internal stress during the charge and discharge process, while maintaining good electronic conductivity, thereby improving its cycle stability and charge and discharge performance at high rates.
[0110] In some embodiments, in S3, the pickling solution is at least one of hydrochloric acid, nitric acid, formic acid, and acetic acid. The concentration of HCl in the hydrochloric acid is 0.05 to 1 mol / L, and the concentration of HNO3 in the nitric acid is 0.05 to 1 mol / L. These pickling solutions can effectively remove impurities from the second precursor and ensure that the second precursor has good structural stability.
[0111] In some embodiments, in S4, the third precursor, the pitch, and the oxide are mixed by ball milling. Ball milling is a commonly used mixing method with low cost and simple operation.
[0112] In some embodiments, in S5 , the second sintering process is performed at a temperature of 850° C. to 950° C. and for a time of 2.5 h to 7.5 h.
[0113] Controlling the temperature of the second sintering process within the above range helps to further promote the disproportionation reaction between the silicon particles in the oxide catalytic core and the unreacted silicon dioxide to generate SiO x, and the asphalt can be fully carbonized to form a stable coating layer, improving the Si / SiO x / C composite material surface properties, reducing Si / SiO x / C composite material, increasing the specific surface area of Si / SiO x First coulombic efficiency and cycling stability of / C composite materials.
[0114] In the fourth typical embodiment of the present application, a Si / SiO x Application of Si / SiO / C composite materials in negative electrode materials x The Si / SiO / C composite material is the Si / SiO x / C composite material, or Si / SiO prepared by the preparation method in the second embodiment of the present application or the third embodiment of the present application x / C composite materials. Due to the above Si / SiO x The carbon / carbon composite material has good electrochemical properties and is suitable for use as a negative electrode material in lithium-ion batteries to improve the electrochemical properties of lithium-ion batteries.
[0115] The present application is further described in detail below with reference to specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in this application.
[0116] Some of the materials in the embodiments and comparative examples are as follows:
[0117] Coal liquefaction oil residue: China Shenhua Coal to Liquids Chemical Co., Ltd., its composition is shown in Table 1-1 and Table 1-2;
[0118] Table 1-1 Industrial analysis and elemental analysis of coal liquefaction oil residue (mass fraction) Unit: %
[0119]
[0120]
[0121] Table 1-2 Ash composition analysis of coal liquefaction oil residue (mass fraction) Unit: %
[0122] <![CDATA[SiO2]]> <![CDATA[Al2O3]]> <![CDATA[Fe2O3]]> CaO MgO <![CDATA[SO3]]> <![CDATA[TiO2]]> <![CDATA[K2O]]> <![CDATA[Na2O]]> <![CDATA[P2O5]]> 12.18 6.58 33.18 21.21 1.30 22.30 0.93 - 1.96 0.36
[0123] Nano-silicon powder: average particle size of 100 nm, JLSi-NC100, Ningbo Jinlei Technology;
[0124] Asphalt: Coal liquefaction asphalt (softening point 252°C, ash content <0.05%), China Shenhua Coal to Liquid Chemical Co., Ltd.
[0125] Example 1
[0126] This application Si / SiO x An embodiment of a Si / SiO / C composite material. x The preparation method of the / C composite material is as follows:
[0127] S1, placing 20 g of coal liquefaction oil residue, 4 g of nano-silicon powder, and 20 mL of tetrahydrofuran in a ball mill, setting the speed of the ball mill to 800 r / min, using zirconia ceramic balls for grinding, and milling uniformly to obtain a first precursor;
[0128] S2, performing a first sintering treatment on the first precursor under argon, with the first sintering temperature being 1050° C., the time being 180 min, and the argon flow rate being 150 mL / min. After the furnace is cooled to room temperature, the sintered product is taken out to obtain a second precursor;
[0129] S3, washing the second precursor with hydrochloric acid having a HCl concentration of 0.5 M, acid-washing and filtering three times, then washing with deionized water until the washing liquid is neutral, and drying to obtain a third precursor;
[0130] S4, placing 10 g of the third precursor, 4 g of asphalt, and 2 g of MgO in a ball mill, and milling them to obtain a fourth precursor;
[0131] S5, the fourth precursor is subjected to a second sintering treatment under a nitrogen atmosphere, the second sintering temperature is 900 ° C, the time is 4.5 hours, the nitrogen flow rate is 150 mL / min, the furnace is cooled to room temperature, the sintered product is taken out, ground, and passed through a 300 mesh sieve to obtain Si / SiO x / C composite materials.
[0132] Example 2
[0133] This application Si / SiO x An embodiment of a Si / SiO / C composite material. x The difference between the preparation method of the Si / SiO composite material and that of Example 1 is that S3 to S5 are omitted, and the second precursor is ground in S2 and passed through a 300-mesh sieve to obtain Si / SiO x / C composite materials.
[0134] Example 3
[0135] This application Si / SiO x An embodiment of a Si / SiO / C composite material. x The differences between the preparation method of the / C composite material and that of Example 1 are as follows:
[0136] In S1, the mass of the coal liquefaction oil residue extract is 12 g, and the mass of the nano-silicon powder is 8 g;
[0137] In S2, the first sintering process is performed at a temperature of 1300°C and for 70 minutes;
[0138] In S4, the mass of the third precursor is 20 g, the mass of asphalt is 2 g, and the mass of MgO is 2 g;
[0139] In S5, the second sintering treatment is performed at a temperature of 850° C. for 7.5 hours.
[0140] Example 4
[0141] This application Si / SiO x An embodiment of a Si / SiO / C composite material. x The differences between the preparation method of the / C composite material and that of Example 1 are as follows:
[0142] In S1, the mass of the coal liquefaction oil residue extract is 20 g, and the mass of the nano-silicon powder is 2 g;
[0143] In S2, the first sintering process is performed at a temperature of 900°C and for 300 min;
[0144] In S4, the mass of the third precursor is 2 g, the mass of asphalt is 6 g, and the mass of MgO is 2 g;
[0145] In S5, the second sintering treatment is performed at a temperature of 950° C. for 2.5 hours.
[0146] Comparative Example 1
[0147] A silicon-based composite material, the preparation method of which is different from that of Example 1 only in that S3 is omitted.
[0148] Comparative Example 2
[0149] A silicon-based composite material, the preparation method of which is different from that of Example 1 only in that no asphalt is added in S4.
[0150] Comparative Example 3
[0151] A silicon-based composite material, the preparation method of which is different from that of Example 1 only in that MgO is not added in S5.
[0152] Comparative Example 4
[0153] A silicon-based composite material, the preparation method of which is different from that of Example 1 only in that no nano-silicon powder is added in S1.
[0154] Comparative Example 5
[0155] A silicon-based composite material, the preparation method of which is different from that of Example 1 only in that: in S2, the temperature of the first sintering treatment is 800°C.
[0156] Comparative Example 6
[0157] A silicon-based composite material, the preparation method of which is different from that of Example 1 only in that: in S2, the time of the first sintering treatment is 60 minutes.
[0158] Performance Testing
[0159] Half-cell preparation: The Si / SiOx / C composite material, silicon-based composite material, polyvinylidene fluoride, and conductive carbon black in the embodiment and comparative example were respectively placed in a ball mill at a mass ratio of 7.5:1.5:1, and an appropriate amount of deionized water was added. The ball mill was milled for 30 minutes, and the ball mill was stopped for 1 minute every 4 minutes and then reversed. The slurry was taken out and placed on a carbon-coated copper foil, and then evenly coated with a 15 μm scraper. The coating was vacuum-dried at 100 ° C for 12 hours. After drying, the coating thickness was 14 ± 0.1 μm. After taking it out, it was cut into discs with a diameter of 14 mm for later use; then, in a glove box, a negative electrode shell-lithium sheet-diaphragm-electrode sheet-stainless steel gasket-spring-positive electrode shell was assembled into a CR2032 type button half-cell. The interior was filled with 150 μL of electrolyte. The solute in the electrolyte was LiPF6 with a concentration of 1 M. The solvent was a mixture of DMC, EC, and EMC in a volume ratio of 1:1:1. The diaphragm was a Whatman GF / F glass fiber diaphragm.
[0160] Half-cell test: The electrochemical performance of the prepared half-cell is tested by constant current charge and discharge method, mainly including the first cycle reversible specific capacity (C 1st ), first cycle coulomb efficiency (CE 1st ), reversible specific capacity retention rate after 100 cycles (C 100th / C 1st ), the test conditions are: current density of 0.05A / g, operating voltage of 0-1.5V, number of cycles of 100, and the test equipment is Shenzhen Xinwei CT-4008T-5V20mA battery tester; the test results are shown in Table 2.
[0161] Table 2
[0162]
[0163] From the above test results, it can be seen that the Si / SiO x / C composite materials have good electrochemical properties. x The first-cycle reversible specific capacity of the half-cell made of the C / C composite material as the negative electrode material can reach more than 750mAh / g, the first-cycle coulombic efficiency can reach more than 78%, and the reversible specific capacity retention rate after 100 cycles can reach more than 75%. It has good cycle stability, good first-cycle coulombic efficiency and excellent electrochemical performance.
[0164] Example 2 did not undergo acid washing and secondary coating, and its capacity, initial coulombic efficiency, and cycle stability were slightly inferior to those of Example 1. Its process flow was simple.
[0165] S3 is omitted in Comparative Example 1. Compared with Example 2, the content of metal oxide and metal silicate is increased, and the thickness of the carbon coating layer is also significantly increased, which will affect the specific capacity of the negative electrode material. In addition, due to the excessive content of metal silicate and metal oxide, the diffusion distance of lithium ions is increased, which affects the charge and discharge performance of the negative electrode material. Its first coulombic efficiency and cycle performance are also relatively poor.
[0166] In Comparative Example 2, no asphalt was added, and surface defects were generated after pickling and could not be eliminated, resulting in poor electrochemical performance.
[0167] In Comparative Example 3, MgO was not added, and the metal oxides and metal silicates lost after pickling could not be compensated, and the SiO x content, which makes it difficult to improve the cycle performance and first coulombic efficiency of the composite material, resulting in poor overall electrochemical performance.
[0168] In Comparative Example 4, nano-silicon powder was not added, and its capacity was low, the lithium insertion performance of the negative electrode material was poor, and the conductivity was also poor, resulting in a decrease in its overall electrochemical performance.
[0169] The temperature or time of the first sintering treatment in Comparative Examples 5 to 6 is relatively low, which is insufficient to allow the disproportionation reaction to occur fully, or to allow silicon dioxide to react with metal oxides to form metal silicates, which has a great impact on the stability of the silicon-based composite material, and it is difficult to form a stable SEI film during the charge and discharge process, resulting in its poor electrochemical performance.
[0170] The above description is merely a preferred embodiment of the present application and is not intended to limit the present application. Various modifications and variations are possible for those skilled in the art. Any modifications, equivalent substitutions, or improvements made within the spirit and principles of the present application shall be included within the scope of protection of the present application.
Claims
1. A Si / SiO x / C composite material, characterized in that The core comprises a carbon matrix and silicon particles, SiO2 and SiO3 supported in the carbon matrix. x and metal silicate, wherein the coating layer comprises a carbon material; the metal silicate comprises at least one of alkali metal silicate, alkaline earth metal silicate, aluminum silicate, titanium silicate, and zinc silicate.
2. Si / SiO according to claim 1 x / C composite material, characterized in that Includes at least one of the following features: (1) The alkali metal silicate is at least one of potassium silicate and sodium silicate; (2) The alkaline earth metal silicate is at least one of magnesium silicate and calcium silicate; (3) The average particle size of the silicon particles is 10 nm to 5000 nm; (4) the SiO x The average particle size is 20nm~5000nm; (5) The average particle size of the metal silicate is 30 nm to 5000 nm; (6) The average thickness of the coating layer is 0.02 μm to 20 μm; (7) the Si / SiO x The average particle size of the / C composite material is 0.05μm to 30μm.
3. A Si / SiO x A method for preparing a / C composite material, characterized in that: The steps include: S1, mixing the ash-containing raw material with nano-silicon powder to obtain a first precursor; S2, sintering the first precursor under nitrogen or inert gas, crushing and sieving to obtain the Si / SiO x / C composite materials; The mass fraction of ash in the ash-containing raw material is 20% to 40%, the mass fraction of carbon in the ash-containing raw material is 55% to 80%, the mass fraction of silicon dioxide in the ash is 10% to 20%, and the mass fraction of metal oxide in the ash is 60% to 70%, wherein the metal oxide includes at least one of alkali metal oxide, alkaline earth metal oxide, aluminum oxide, titanium oxide, and zinc oxide; In S2, the sintering treatment is performed at a temperature of 900° C. to 1500° C. and for a time of 70 min to 300 min.
4. The preparation method according to claim 3, characterized in that Includes at least one of the following features: (1) The ash-containing raw material is at least one of coal liquefaction oil residue extract, coal, coal tar, and petroleum asphalt; (2) The average particle size of the nano-silicon powder is 10 nm to 5000 nm; (3) The alkali metal oxide includes at least one of potassium oxide and sodium oxide; the alkaline earth metal oxide includes at least one of magnesium oxide and calcium oxide; (4) The mass ratio of the ash-containing raw material to the nano-silicon powder is (1-10):
1.
5. The preparation method according to claim 3 or 4, characterized in that Includes at least one of the following features: (1) In S1, the ash-containing raw material and the nano-silicon powder are mixed by wet ball milling; (2) In S2, the inert gas is at least one of argon and helium; (3) In S2, sieving is performed using a sieve having a mesh size of 150 to 350 meshes.
6. A Si / SiO x A method for preparing a / C composite material, characterized in that: The steps include: S1, mixing the ash-containing raw material with nano-silicon powder to obtain a first precursor; S2, performing a first sintering treatment on the first precursor under nitrogen or a first inert gas to obtain a second precursor; S3, acid-washing, water-washing, and filtering the second precursor to obtain a third precursor; S4, mixing the third precursor, asphalt, and oxide to obtain a fourth precursor; S5, performing a second sintering treatment on the fourth precursor under nitrogen or a second inert gas, crushing and sieving to obtain the Si / SiO x / C composite materials; The mass fraction of ash in the ash-containing raw material is 20% to 40%, and the mass fraction of carbon in the ash-containing raw material is 55% to 80%; the mass fraction of silicon dioxide in the ash is 10% to 20%, and the mass fraction of metal oxides in the ash is 60% to 70%, wherein the metal oxides include at least one of a first alkali metal oxide, a first alkaline earth metal oxide, aluminum oxide, titanium oxide, and zinc oxide; and the oxides include at least one of a second alkali metal oxide, a second alkaline earth metal oxide, aluminum oxide, titanium oxide, and zinc oxide; In S2, the temperature of the first sintering treatment is 900° C. to 1500° C., and the time is 70 min to 300 min.
7. The preparation method according to claim 6, characterized in that Includes at least one of the following features: (1) The ash-containing raw material is at least one of coal liquefaction oil residue extract, coal, coal tar, and petroleum asphalt; (2) The average particle size of the nano-silicon powder is 10 nm to 5000 nm; (3) The first alkali metal oxide and the second alkali metal oxide each independently include at least one of potassium oxide and sodium oxide; the first alkaline earth metal oxide and the second alkaline earth metal oxide each independently include at least one of magnesium oxide and calcium oxide; (4) The asphalt includes at least one of coal liquefaction asphalt, petroleum asphalt, coal tar asphalt, synthetic asphalt, and natural asphalt; (5) The mass ratio of the ash-containing raw material to the nano-silicon powder is (1-10):1; (6) The mass ratio of the third precursor, the asphalt, and the oxide is (1-10):(1-3):
1.
8. The preparation method according to claim 6, characterized in that Includes at least one of the following features: (1) In S1, the ash-containing raw material and the nano-silicon powder are mixed by wet ball milling; (2) In S1, the ash-containing raw material and the nano-silicon powder are mixed by wet ball milling, and the solvent of the wet ball milling is at least one of alcohol, ketone, ester, alkane, and aromatic hydrocarbon; (3) The first inert gas and the second inert gas are each independently at least one of argon and helium; (4) The sieving is performed using a sieve having a mesh size of 150 to 350 meshes; (5) In S3, the pickling solution is at least one of hydrochloric acid, nitric acid, formic acid, and acetic acid; (6) In S4, the third precursor, the asphalt, and the oxide are mixed by ball milling.
9. The preparation method according to any one of claims 6 to 8, characterized in that In the above S5, the temperature of the second sintering treatment is 850° C. to 950° C., and the time is 2.5 hours to 7.5 hours.
10. A Si / SiO x The application of the / C composite material in the negative electrode material is characterized in that: The Si / SiO x The Si / SiO / C composite material is the Si / SiO x / C composite material, or Si / SiO prepared by the preparation method according to any one of claims 3 to 9 x / C composite materials.